Virtual community medicine in sparsely populated regions: A case study from Northern Sweden - Koch, Andreas (Archives of Community Medicine and Public Health, 2024)
The short case study outlines the potential that Virtual Health Rooms (VHRs) can exhibit to mitigate a lack of public health services and community medicine infrastructure in sparsely populated and demographically ageing regions. Although the VHR idea has its strengths in surmounting a relatively low medical service environment, it is, nonetheless, a technologically driven approach to meet the needs of local residents in rural peripheries. Therefore, the VHR approach has been tested in some Northern Swedish villages and has been evaluated empirically in one of these villages (Storuman). Beyond a dedicated health-driven purpose, Virtual Health Rooms can comprehensively serve as a public meeting point to reduce local social isolation. In this respect, the regional Storuman Hospital functions as a Center for Rural Medicine in a broad sense and aims, among other things, to decentralize public health services to local communities in the rural periphery.